Organoleptic Quality and pH of Silage of Young Corn and Sorghum - Syamsul Hidayat Dilaga; Azhary Noersidiq; Fahrullah Fahrullah (Jurnal Biologi Tropis, 2023)
Effective processing of young corn and sorghum silage can be evaluated based on physical attributes like fragrance, colour, texture, and the properties and transformations that happen in the feed during the ensiling process. These attributes can be employed to assess and establish the quality of the feed. The purpose of this research is to determine the characteristics of young corn and sorghum silage by conducting pH testing and organoleptic analysis. The study used three types of silage: P1 - young corn, P2 - sorghum, and P3 - a mix of young corn and sorghum. The variables examined included colour, aroma, texture, presence of fungi, and pH. The data indicates that the silage produced from young corn and sorghum plants was of high quality. The feed before the silage production process was the same shade, and the end product had a sour scent. Texture-wise, the majority of the silage was slightly rough and not slimy, with no signs of fungal contamination. The pH ranged from 3.63-3.92, confirming the silage's acidic nature. Silage made from young corn and sorghum plants exhibits organoleptic qualities such as a brownish-green hue, mildly fragrant aroma, slightly mushy consistency, and no detected presence of fungus. Moreover, due to its acidic properties resulting from the pH value, it is highly conducive for the proliferation of lactic acid bacteria.